Treatment of landfill leachate evaporation concentrate by a modified electro-Fenton method. Issue 4 (10th February 2022) - Meng, Guangcai; Wang, Yanqiu; Li, Xiao; Zhang, Huan; Zhou, Xinyu; Bai, Zhongteng; Wu, lizhuo; Bai, Jinfeng
ABSTRACT: Landfill leachate evaporation concentrate (LLEC) is difficult to treat due to its complex pollutant composition, which involves large amount of organic matter and inorganic salts such as scaling ions. Because of its high conductivity and high chloride-ion content, this study employed the modified electro-Fenton method with a self-developed iron-loaded cathode to treat LLEC wastewater. The operating variables were optimized according to the response surface methodology where the chemical oxygen demand (COD) removal efficiency was considered as the response based on single-factor experiments. A second-order polynomial regression model was obtained, and an application experiment revealed that it could be applied to determine LLEC treatment conditions. The removal rates of COD and colour were 100% and 99.8%, respectively, under the optimal operating conditions of an initial pH of 6, electrode spacing of 1 cm and applied voltage of 9 V. Three-dimensional fluorescence spectroscopy demonstrated that the humic acid and fulvic acid pollutants were almost completely removed. Scanning electron microscopy and energy dispersive spectroscopy analysis showed that the iron catalyst was loaded in activated carbon pores and exhibited almost no consumption during the reaction, which effectively solved the problem of iron sludge precipitation caused by electro-Fenton oxidation technology. The atomic distribution in the crystal was also analyzed by X-ray diffraction. The specific energy consumption of electrochemical oxidation was 0.498 Wh·mg −1 COD. The results indicate that the modified electro-Fenton technique with the proposed novel cathode is an effective method for treating LLEC. GRAPHICAL ABSTRACT: UF0001